Executive orders - Clancy, Tom, 1947-2013 (Clancy, Tom, 1947-2013. Jack Ryan novel, 1997)
Jack Ryan becomes president by sheer accident when the former president, most of Congress, the Cabinet and the Supreme Court are bombed out of existence. Ryan must jump in to discover who did it, all the while contending with the threat of military takeover and covert biological warfare.